LA REFORMA A LOS ART. 576,583,584 DEL CÓDIGO DE TRABAJO, PARA EVITAR SU DEMORA , HARA POSIBLE LA GARANTIA AL DEBIDO PROCESO Y SEGURIDAD JURDICA, Y LA SOLUCIÓN EN SEDE JUDICIAL DE LOS PROBLEMAS DERIVADOS DEL TRABAJO - TORRES SANTIN, SONIA VILMA (2016)
The analysis of the remainig problems in the labor procedure determines that the effective exercise of the right, understood as the direct application of legal rules that permit effective defense of those rights into that may be violated, as in oral proceedings in labor predominates the principle of concentration, with the result that the time elapsed since the filing of complaint, hearings, reproduction evidence, arguments and judgments should be minimal, since the legislature has forgotten that orality must achieve speed concentration, effectiveness and efficiency,without interruption of any kind of this research is to suggest revelant aspect through a through and ojective analysis of the problems ralted to working procedure so that this work is somehow directed to discern and disseminate mechanisms to comply with the terms of the constitution in the labor code.The law must be consisitent whit the current constitution ´´that speaks of living, wages, the rights of all´´